PENGARUH CARA PERAWATAN TERHADAP KUAT TEKAN DAN KUAT LENTUR HIGH EARLY STRENGTH FIBER REINFORCED CONCRETE - Yogo Edi Prasetyo, Slamet Widodo (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2015)
ABSTRACTThis research aims to compressive strength in fiber-reinforced concrete treatment withconventional treatment, the treatment compressive strength fiber-reinforced concrete curingcompound by treatment, Strong bending in the fiber-reinforced concrete maintenance treatmentat curing compound. Treatment of fiber-reinforced concrete accelerated hardening processusing two methods of treatment and care of concrete with concrete soaked with curringcompound. This research used 24 samples of the specimen cylinder with a diameter of 15 cmand 30 cm, to test a row of concrete at the age of 3 days, 7 days, 14 days and 28 days. Flexuralstrength testing 24 samples of concrete using beam specimen with a length of 53 cm, height 10cm width 10 cm, tests are carried out in succession at the age of 3 days, 7 days, 14 days and28 days. This study took this 3 sample test specimens for each type of testing at a certain age.The results showed that of the compressive strength in fiber-reinforced concrete treatment withconventional treatment at the age of 3 days: 35.36 N/mm2, 7 days: 41.87 N/mm2, 14 days: 43.32N/mm2, and 28 days: 48.66 N/mm2. Flexural strength on fiber-reinforced concretetreatment withconventional treatment in a row at the age of 3 days: 8:30 N/mm2, 7 days: 7:58 N/mm2, 14 days:8.66 N/mm2, and 28 days: 8.85 N/mm2. Compressive strength in steel with treatment of fibrousconcrete curing compound treatments successively at the age of 3 days: 27.34 N/mm2, 7 days:30.46 N/mm2, 14 days: 37.53 N/mm2, 28 days: 37.72 N/mm2. Flexural strength in the treatmentof fiber-reinforced concretecuring compound treatment at successively at the age of 3 days:7:45 N/mm2, 7 days: 6.75 N/mm2, 14 days: 7.86 N/mm2, 28 days: 8.98 N/mm2. Compressivestrength test with care soaked 21.25% higher than the curing compound, and flexural strengthtest with marinated treatments 7.25% higher than that of concrete curing compound withmarinated care is stronger than concrete curing compound treatment and how treatment mayaffect the resulting strength of the concrete.Keywords: Compressive strength, Curing compound, Flexural strength